Design and Development of Emulgel Preparation Containing Diclofenac Potassium - Deshmane, Dr. Subhash V. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: This study aims to explore the potential of emulgel in enhancing the topical delivery of diclofenac potassium. Materials and Methods: Emulgel formulations of diclofenac potassium were prepared using different concentrations of gelling agent’s Carbopol-940. Tween-20 and span-20 were used as emulsifiers, and propylene glycol as a humectant in gel was selected for the preparation of emulgel. The effect of concentration of gelling agent on the drug release from the prepared emulgel was investigated. The compatibility study was conducted using fourier-transform infrared (FTIR) and differential scanning calorimetry (DSC). The formulated emulgel was characterized for their physical appearance, pH determination, viscosity, spreadability, swelling index, drug content, skin irritation test, microbial test, and in vitro diffusion study. Result and Discussion: FTIR and DSC study proved that the drug and excipients are compatible with each other. All the prepared formulations showed acceptable physical properties, homogeneity, consistency, spreadability, viscosity, and pH value. After 6 h of drug diffusion study, the formulation EG4 showed consistent release of the drug form emulgel with 89.72%. It might be due to the higher concentration of the emulsifying agents and the 2% concentration of the gelling agent. Conclusion: The study was concluded that the preparation was more stable than single emulsion and also improved desired properties for transdermal application. The emulgel preparation is the best choice for the water‑insoluble drug.